Pendampingan Kegiatan Mabit (Malam Binaan dan Takwa) dalam Meningkatkan Kualitas Pendidikan Karakter di Sekolah Dasar Islam Cahaya Permata Kabupaten Malang - Mochamad Nurcholiq; Kholiqul Indriarto Altalka; Zen Amrullah (Ngabekti: Jurnal Pengabdian kepada Masyarakat, 2026)
Character education at the elementary school level requires learning experiences that go beyond classroom instruction and allow students to practice positive values in real situations. One of the programs implemented by Cahaya Permata Islamic Elementary School in Malang Regency is MABIT (Faith and Piety Development Night). This community service project aimed to assist the management of the MABIT program as an effort to strengthen students’ character development. The program employed the Asset Based Community Development (ABCD) approach and involved school leaders, teachers, students, and parents throughout the process. The assistance included asset mapping, program planning, implementation, and evaluation activities. MABIT was conducted over two days and one night through a series of activities, including congregational prayers, Qur’anic revision sessions, field exploration, educational competitions, campfire activities, and environmental clean-up programs. The experience showed that the program could be implemented in a well-organized manner through collaboration among teachers, committees, and parents. Beyond its religious dimension, MABIT provided students with opportunities to develop discipline, responsibility, cooperation, and independence through direct participation in various activities. The program also offered the school a practical way to integrate experiential learning into character education and to create learning experiences that are closely connected to students’ daily lives.